KAJIAN KECEPATAN PERKECAMBAHAN KENERAK MENGGUNAKAN HORMON 2,4-D DAN BAP SECARA IN VITRO (The Study of Germination Rapids on Kenerak using 2,4-D and BAP hormones by in vitro methods) - Mahadi, Imam (Jurnal Pilar Sains, 2007)
Kenerak (Goniothalamus umbrosus) is one species from genus of Goniothalamus and becomes sources ofimportant traditional medicines among local people in Southeast Asia.Goniothalamus plants areconsidered to have great sources of pharmaceuthecial substances. The goniothalamine has a function bothas an anti breast cancer agent and as an abortive agent for early pregnancy. Based on this the preliminarystudies was carried out on germination rapids of kenerak using seed explants showed that best result forgermination rapids on MS A4 (0,5 mg/l 2,4-D) medium after 3-8 weeks culture and totals germination onE6 (2,0 mg/l 2,4-D + 0,5 mg/l BAP) medium 80%. Compered convensional methods is very long timeabout 6-12 moons. In vitro technique can be used for overcoming dormancy seeds of kenerak.Key words: Kenerak, 2,4-D, BAP, Seed .